Analysis of Physical Capacity and Somatotype In Middle Distance and Long Distance Running Athletes 12-15 Years Old In PASI, Pacitan Regency - Ilham Satrio Pambudi; Dita Yuliastrid; Roy Januardi; Soni Sulistyarto (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Middle-distance and long-distance runners have different characteristics. The purpose of this study was to determine the differences in physical capacity and somatotype types between middle-distance and long-distance runners aged 12-15 years at PASI Pacitan. The quantitative descriptive research method with a cross-sectional study design to identify physical capacity and somatotype, the sample consisted of 12 runners. The determination of the research sample used purposive sampling. The results of VO2 max of middle-distance athletes in the moderate, good and excellent categories were 33.33%, respectively. In long-distance athletes, the good category was 33.33% and the excellent category was 66.66%. The somatotype results in middle-distance runners were dominated by the central type which reflects a balance between endomorph, mesomorph, and ectomorph elements, followed by mesomorph, ectomorph, and mesomorph-endomorph. In long-distance runners, the dominant somatotype was ectomorph, followed by mesomorph-ectomorph and mesomorph.